Mental and physical health‐related quality of life in patients with hepatitis C is related to baseline comorbidities and improves only marginally with hepatitis C cure. Issue 4 (April 2018) - Thuluvath, Paul J.; Savva, Yulia
Abstract : N/A: The objective of the study was to analyze the relationship between patient characteristics and the health‐related quality of life (HRQoL) among patients with hepatitis C at the start of treatment, 2–12 weeks of treatment and ≥3 months post treatment using Short‐Form 36 (SF‐36). The eight domains and two composite scores of SF‐36 were analyzed using 236 individuals. Compared to US general population norms, on average, the physical health scores were significantly lower for the studied hepatitis C population, while the differences related to mental health were between zero and small. For a physical health composite score, the treatment effect was between medium and large (0.70, 0.66, and 0.64 at the baseline and follow‐ups), and for a mental health composite score it was close to zero. After controlling for demographic factors, the mixed‐effects models demonstrated that HRQoL significantly improved only for general health during the treatment and vitality during post treatment. The strongest predictor of HRQoL at the two follow‐up periods was HRQoL at baseline of the same domain. The ordinal logistic regressions showed that at the baseline, the strongest negative predictors of HRQoL in most of the domains were hypertension, diabetes, high BMI, high number of comorbidities including pulmonary comorbidities, low hemoglobin, and public health insurance. Considering that the improvement in HRQoL sustained after treatment only for a mental (vitality) domain, the main determinants of quality of life of the patients with hepatitis C were comorbidities.